How does subsidy change a firm's market power? The case of China's rice processing industry - Jiawu Dai; Xun Li (Journal of Applied Economics, 2020)
The effect of subsidy on firms' market power is controversial and unclear. In this article, we investigate such effect through an unbalanced panel data at firm level. Empirical results indicate that subsidy weakens the market power of firms subsidized. We then verify our hypothesis for this result that striving for subsidy through building or keeping relationship with governments will lead to higher administration and selling expense, and therefore lower market power, given that the rice processing industry is relatively competitive due to its low entry barrier and high homogenous product. Compared with non-state-owned enterprises, state-owned enterprises are found to be weaker in market power, to be higher in administration expense and to be lower in selling expense, which are well consistent with China's reality. Finally, robustness test consolidates our conclusions.
Keywords: 330; market power; non-SOEs; SOEs; Subsidy